Decision of E-Commerce Services for Students Using Analitycal Hierarchy Process (AHP) as Decision Support for E-Commerce Shopping Service Selection - Nur Rival Dwi Apria Arta; Nur Alia Qorina; Izzat Muhammad Haifa Nabil (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2026)
Online shopping is becoming a habit among the public due to the convenience it offers. This research aims to help consumers choose the appropriate e-commerce application, using the Analytic Hierarchy Process (AHP) method and involving 33 respondents. The three e-commerce platforms analyzed are Shopee, Tokopedia, and Lazada. The results show that Shopee ranks first in all evaluated criteria, namely price, delivery speed, transaction security, and product completeness. Thus, Shopee has become the most chosen platform by respondents. The first and subsequent rankings in the Price Criteria = Shopee with 53.27%. Delivery Speed Criteria = Shopee 36.8%. Transaction Security Criteria = Shopee 54.14%. Product Completeness Criteria = Shopee 63.07%. If we look at the processed data we obtained, the Shopee application was chosen 4 times, or among all the criteria, Shoope is in the first position.